KARAKTERISTIK UTAMA DESAIN PENELITIAN MIXED METHODS DAN IMPLIKASINYA TERHADAP KUALITAS PENELITIAN - Nurul Masruni (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to examine the main characteristics of mixed-methods research design and its implications for research quality. The method used in writing this article is a literature review (library research) with a descriptive-analytical approach. Data were obtained through a review of various relevant literature, including books, scientific articles, and other academic sources discussing the concepts, characteristics, design, and application of mixed methods in research. Data analysis was conducted using content analysis techniques to identify and synthesise various expert perspectives on mixed methods. The findings indicate that the key characteristics of mixed methods research designs include the integration of quantitative and qualitative data, the use of triangulation, design flexibility, the utilisation of various data sources, and a focus on a comprehensive understanding of the phenomena under investigation. These characteristics have positive implications for research quality through enhanced validity, reliability, credibility, and depth of data analysis. Furthermore, mixed methods can yield more comprehensive findings by combining the strengths of quantitative and qualitative approaches within a single study. Nevertheless, the application of mixed methods also faces challenges in the form of design complexity, greater demands on time and resources, and the requirement for high methodological competence. Therefore, an adequate understanding of the characteristics and procedures for applying mixed methods is a crucial factor in producing high-quality research that is relevant to the advancement of scientific knowledge.